Boarding School Management on Students’ Character Building in An-Nawawiyyah Islamic Junior High School Rembang - Arifah, Mukhsinatul; Murwatiningsih, Murwatiningsih; Harlanu, M. (Educational Management, 2019)
The research aims to describe (1) planning; (2) realization; and (3) supervision of boarding school on students’ character building in An-Nawawiyyah Islamic Junior High School Rembang. The method of this research uses qualitative approach. The data sources are from informant (vice headmaster, teachers, caretaker/Islamic preacher, and students), observation and document. The data collection technique is by using interview, observation, and documentation. In addition, the data testing technique is done by triangulation. Besides, the data analysis technique is by using some phases consisting of data reduction, data showing, and verification. The research result showed that the service of character building of An-Nawawiyyah Islamic Junior High School Rembang students was integrated in the students’ activities in the classroom and outside the classroom. All policy was planned by the school and Islamic boarding school. The planning of integrated character education between school curriculum and Islamic boarding school program is done by determining executing team of character building namely Islamic preacher of Islamic boarding school. The scheduling and the programming of character building in organization were realized in form of cooperation among schools’ community and Islamic Junior High School. The realization was integrated in every student’s activities. The supervision was addressed to the implementation of students’ discipline regulation. From the research result, it can be concluded that character building of An-Nawawiyyah Islamic Junior High School Rembang students is not separated from the role of boarding school. Boarding school of An-Nawawiyyah Islamic Junior High School Rembang can build the attitude of politeness, discipline, honesty, responsibility, independence, nationalism, and environmental caring.